2020
DOI: 10.1108/tg-03-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the adoption of e-democracy: an empirical evaluation based on a citizen-centric approach

Abstract: Purpose This study aims to explore the factors influencing the intention to use e-democracy. The literature depicted conflicting results regarding such domain and especially in the Middle East, where the authors aim at establishing a solid view of the discipline. Design/methodology/approach A research model was developed based on the theory of planned behavior, technology acceptance model and unified theory for acceptance and use of technology-2. The model hypothesized that perceived public value (PPV), ease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…The study findings demonstrate the significance of P_OUTCOME in predicting citizens' acceptance (H10). This finding confirms previous studies' suggestion that citizens would accept participation when they feel that their opinions would be embedded in the government decision‐making process (de Jong et al, 2019; Hujran et al, 2020; Lee, 2017). In the context of Jordan, much evidence has highlighted the substantial role of the outcomes perceived from using participatory and e‐democracy systems on citizens' acceptance (Alomari, 2016; Hujran et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study findings demonstrate the significance of P_OUTCOME in predicting citizens' acceptance (H10). This finding confirms previous studies' suggestion that citizens would accept participation when they feel that their opinions would be embedded in the government decision‐making process (de Jong et al, 2019; Hujran et al, 2020; Lee, 2017). In the context of Jordan, much evidence has highlighted the substantial role of the outcomes perceived from using participatory and e‐democracy systems on citizens' acceptance (Alomari, 2016; Hujran et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the results of related studies (e.g., Zolotov et al, 2018; Zolotov et al, 2019; Panopoulou et al, 2021), indicating that PU positively impacts citizens' ACCEPT of using e‐participation. In the MENA context, the ATT and PU were significant factors in citizens' acceptance to use e‐democracy and e‐voting tools in Jordan (Alomari, 2016; Hujran et al, 2020). Furthermore, ATT was a significant predictor of Saudi citizens' intention to engage in e‐participation activities (Alharbi et al, 2016; Alrashedi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ketchen [74] stated that the PLS-SEM is adequate for validating predictive power and estimating significantly complex models. Accordingly, PLS-SEM has been used by many scholars in various fields such as e-commerce [75][76][77][78][79][80][81], information systems [82], e-government [83,84], and educational technology-related research [85][86][87][88]. Corresponding with Anderson and Gerbing [89], data analysis using SmartPLS v.3.3.3 was performed throughout two key analytical stages.…”
Section: Resultsmentioning
confidence: 99%
“…In the north of India, a study was conducted to investigate the factors affecting the user' acceptance for (3G) technology. The results revealed that hedonic motivations have a significant relationship with the intention to use (Kumar, 2013;Hujran, Abu-Shanab & Aljaafreh, 2020). According to (Alalwan et al, 2017).…”
Section: Hedonic Motivationmentioning
confidence: 99%